Nine decades of dealing with diversity - Czegledi, Sandor (ELOPE (Ljubljana), 2020)
The paper examines the shifting orientations towards languages and linguistic diversity in the United States by analysing relevant Congressional and presidential documents from the beginning of the American nation-building experience until the outbreak of the Civil War. The investigation focuses on the legislative activities of the Continental Congress and those of the first thirty-six federal Congresses as recorded primarily in the Journals of the respective legislative bodies. The presidential documents of the first fifteen Chief Executives, from George Washington to James Buchanan, are examined from the same perspective. The results indicate that the most salient language policy development of the post-1789 period was the shift from the symbolic, general language-related remarks towards the formulation of substantive, general policies, frequently conceived in an assimilation-oriented spirit in the context of territorial expansion. Although presidents were considerably more reluctant to address language-related matters than the federal legislature, the need to revise the statutes of the United States was recognised as a presidential priority as early as the 1850s.
Keywords: Congress; jezikovna ideologija; jezikovna politika; Kongres; language ideology; language policy; obdobje pred ameriško državljansko vojno; pre-Civil War era; predsedništvo; Presidency; United States; Združene države Amerike